Sexual Satisfaction Changes Reported by Men After Their Partners' Robotic-Assisted Laparoscopic Sacrocolpopexies. Issue 5 (September 2019) - Culligan, Patrick J.; Haughey, Sean; Lewis, Christa; Priestley, Jennifer; Salamon, Charbel
Abstract : Objectives: This study aimed to compare the preoperative and postoperative sexual satisfaction reported by male sexual partners of women undergoing surgical correction of pelvic organ prolapse. Methods: This was a single-center prospective cohort study. Heterosexual, sexually active English-speaking couples in which the women were planning to undergo robotic-assisted laparoscopic sacrocolpopexy for correction of pelvic organ prolapse were eligible for enrollment in the study. Validated sexual function questionnaires—the Sexual Experience Questionnaire (SEX-Q; Mulhall et al. J Sex Med . 2008) and Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire-12 (Rogers, et al. Int Urogynecol J Pelvic Floor Dysfunct . 2003)—were used to evaluate preoperative and postoperative male and female sexual experience, respectively. These preoperative scores were compared using paired t tests. The Student t and the Mann-Whitney tests were used to compare study-eligible couples with noneligible couples and to compare study participants with nonparticipants. Results: During the study enrollment period, 92 couples met the inclusion criteria and 45 of those were enrolled. Complete data sets of preoperative and postoperative questionnaires were obtained for 36 couples. After their partners' successful reconstructive surgery, male study subjects reported improved total SEX-Q scores (mean ± SD, 71 ± 16.7 vs 76.5 ± 17.8; P = 0.025). Within the subscales of the SEX-Q, there was significant improvement between preoperative and postoperative "individual satisfaction" scores (mean ± SD, 65.7 ± 16.8 vs 78.9 ± 17.5; P < 0.0001), but not within the "erectile dysfunction" or "couple satisfaction" subscales. Female partners reported improved Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire-12 scores after surgery (mean ± SD, 36.6 ± 5.5 vs 40.0 ± 4.6; P = 0.003). Conclusions: Sexually active heterosexual men and women reported improved sexual experience after successful prolapse repair.